AGE COMPOSITION CHANGES OF RIGA AGGLOMERATION RING - Skadins, Toms (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Over the course of several previous decades the post-socialist countries of Central and Eastern Europe have experienced notable population disposition and composition changes in the vicinity of large cities. Despite this, age composition related studies have rarely paid attention to changes within these city regions. Thus, the aim of this paper is to shed light on age composition changes of Riga agglomeration ring. For this study official statistical data, along with population ageing index is utilized. Changes are studied for the entire ring and its structures of urban and rural areas for the years 2000, 2011 and 2020. Results indicated that, despite a decrease, the 25-44 year old age group remained the most populous. 15-24 year old group had the largest decrease. Pre-working age and the two oldest groups were the ones which had tended to increase the most in comparison to situation in 2000. However, ring and urban areas first saw a decrease of pre-working age population leading up to 2011, followed by a more notable growth. Population ageing index values showed that for all territory types population ageing had slowed after 2011. Also, urban areas of Riga agglomeration have been ageing more rapidly than rural ones. This study was supported by National Research Program Project grant number VPP-IZM-2018/1-0015.